Risk Factors for Proliferative Diabetic Retinopathy in African Americans with Type 2 Diabetes. (3rd March 2016) - Penman, Alan; Hancock, Heather; Papavasileiou, Evangelia; James, Maurice; Idowu, Omolola; Riche, Daniel M.; Fernandez, Marlene; Brauner, Stacey; Smith, Sataria O.; Hoadley, Suzanne; Richardson, Cole; Vazquez, Vanessa; et al.
ABSTRACT: Purpose : To assess personal and demographic risk factors for proliferative diabetic retinopathy in African Americans with type 2 diabetes. Methods : In this prospective, non-interventional, cross-sectional case-control study, 380 African Americans with type 2 diabetes were enrolled. Participants were recruited prospectively and had to have either: (1) absence of diabetic retinopathy after ≥10 years of type 2 diabetes, or (2) presence of proliferative diabetic retinopathy when enrolled. Dilated, 7-field fundus photographs were graded using the Early Treatment Diabetic Retinopathy Study scale. Covariates including hemoglobin A1C (HbA1C ), blood pressure, height, weight and waist circumference were collected prospectively. Multivariate regression models adjusted for age, sex and site were constructed to assess associations between risk factors and proliferative diabetic retinopathy. Results : Proliferative diabetic retinopathy was associated with longer duration of diabetes (odds ratio, OR, 1.62, p < 0.001), higher systolic blood pressure (OR 1.65, p < 0.001) and insulin use (OR 6.65, p < 0.001) in the multivariate regression analysis. HbA1C was associated with proliferative diabetic retinopathy in the univariate analysis (OR 1.31, p = 0.002) but was no longer significant in the multivariate analysis. Conclusions : In this case-control study of African Americans with type 2 diabetes, duration of diabetes, systolic hypertension and insulin use were strong risk factors for the development of proliferative diabetic retinopathy. Interestingly, HbA1C did not confer additional risk in this cohort.